Dietary Content and Potential Health Risks of Metals in Commercial Black Tea in Kampala (Uganda) - Bamuwamye, Michael; Ogwok, Patrick; Tumuhairwe, Vivian; Eragu, Richard; Nakisozi, Henriettah; Ogwang, Patrick E. (Journal of Food Research, 2017)
Tea (Camellia sinensis (L.) Kuntze) is among the most widely consumed non-alcoholic beverages. It is a rich source of essential dietary elements mainly potassium and manganese. Tea may also contain toxic metals such as cadmium and lead which pose a threat to human health because of their toxicity. Twenty samples of commercial black tea in Kampala city were randomly obtained and analysed for potassium, sodium, aluminium, arsenic, cadmium, chromium, copper, iron, mercury, manganese, nickel, lead and zinc using Atomic Absorption Spectrophotometry. Human health risks due to exposure to toxic elements from daily consumption of tea were determined using incremental lifetime cancer risk and non-cancer hazard quotient. Metal contents of black tea sold in Kampala were below international regulatory limits. The estimated daily intake of the elements in two grams of black tea was below the recommended values. Hazard quotient and hazard index were within acceptable range. Total cancer risk levels for all the teas were also within United States Environmental Protection Agency (USEPA) acceptable range. Daily consumption of one cup containing two grams of black tea over a lifetime will promote consumer overall health and wellbeing.
Keywords: Black tea; Heavy metals; Exposure; Cancer risk; Uganda